2011
DOI: 10.1038/hr.2011.19
|View full text |Cite
|
Sign up to set email alerts
|

Non-activated APJ suppresses the angiotensin II type 1 receptor, whereas apelin-activated APJ acts conversely

Abstract: Apelin and its G-protein-coupled receptor APJ are potent regulators of the cardiovascular system. Recent studies have suggested that apelin-APJ reverses the function of angiotensin II (Ang II)-the Ang II type 1 receptor (AT 1 ). However, the mechanism remains unclear because of the accumulating evidences that apelin-APJ may contribute to both cardioprotection and pathological progression. In human embryonic kidney 293 cells, we found that coexpression with APJ significantly suppressed the phosphorylation of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 36 publications
2
31
0
2
Order By: Relevance
“…APJ and AT1 receptor-receptor interactions are presently accounted as the potential molecular mechanism of crosstalk responsible for this reciprocal counter-regulation between apelin and Ang II pathways, since it was observed in vitro that the respective receptors can form heterodimers and that this heterodimerisation influences downstream signaling [7]. Our observations on fetal lung growth are in accordance with others reporting that the proposed effects of the apelin-APJ system are opposite to those of the Ang II-AT1 receptor pathway [7,44].…”
Section: Discussionsupporting
confidence: 91%
“…APJ and AT1 receptor-receptor interactions are presently accounted as the potential molecular mechanism of crosstalk responsible for this reciprocal counter-regulation between apelin and Ang II pathways, since it was observed in vitro that the respective receptors can form heterodimers and that this heterodimerisation influences downstream signaling [7]. Our observations on fetal lung growth are in accordance with others reporting that the proposed effects of the apelin-APJ system are opposite to those of the Ang II-AT1 receptor pathway [7,44].…”
Section: Discussionsupporting
confidence: 91%
“…The AT1R/APJ interaction described here provides a glimpse into the true allosteric nature of receptor heterodimers, in that depending on how they are arranged, striking asymmetries may be detected in how each protomer interacts with ligands and further, how it might signal in a manner distinct from the parent monomeric or homodimeric receptors. Previous studies have demonstrated that activated APJ modulates AT1R signalling in HEK 293 cells (Sun et al, 2011) and in primary vascular smooth muscle cells (Chun et al, 2008;Siddiquee et al, 2011). In one study, there were striking differences detected in the effects of unoccupied and ligand-occupied APJ on AT1R signalling, suggesting distinct allosteric interactions depending on the state of the system (Sun et al, 2011).…”
Section: At1r Are Social Animals-they Interact With Other Gpcrsmentioning
confidence: 99%
“…Such regulation likely depends on the relative abundance of the two receptors in a given tissue. Indeed, others have shown the AT1R is likely to be a signalling hub whose functions are controlled by a number of partner receptors such as the b2AR (Barki-Harrington et al, 2003), the B2 bradykinin receptor (Quitterer et al, 2004) and the apelin receptor (Chun et al, 2008;Siddiquee et al, 2011;Sun et al, 2011).…”
Section: At1r Are Social Animals-they Interact With Other Gpcrsmentioning
confidence: 99%
“…By contrast, it has been proposed that inactivated APJ can form heterodimers with AT1 which suppresses RAS signalling. This inhibitory effect is reduced by the binding of apelin to APJ [33]. In addition to the modulation on AT1R signalling, apelin counteracts RAS by up-regulating ACE2 expression via APJ (Fig.…”
Section: Apelin/apj System Vs Renin-angiotensin System (Ras)mentioning
confidence: 99%